ANALISIS KESALAHAN PENGGUNAAN ORTOGRAFI PADA KETERAMPILAN MENULIS SISWA KELAS X IPS 3 SMA NEGERI 1 MOJOSARI - EPA, DORKAS (LATERNE, 2018)
Keywords: Error analysis, Orthography, Writing skills Learning Germany can not be separated from the four language skills that must be taught simultaneously in the learning. Learning is one of them is the writing skill. Writing skills are an active activity. Similarly, in the put forward by Nurgiyantoro (2001: 271) that Writing is an active, productive, complex and integrated language skills that reward disclosures that are manifested in writing. Based on the observations made there are still errors that are often done by students. Therefore, research is done to analyze what kind of mistakes students make when creating a short dialogue in German. Through this research can be seen what mistakes are often made by students in making a simple dialogue using a very simple language. The error that we can see from the result of this research is error of usage of otrografi especially on punctuation. The formulation of the problem in this research is "Error of Using Punctuation what is done by Student of X Grade 2 of  SMAN 1 Mojosari". The purpose of this study is to "describe the errors in the use of German punctuation language in the writing skills of students of class X Semester 2 SMAN 1 Mojosari".  This research is a descriptive qualitative research. The research data is obtained from a simple dialogue made by students of class X IPS 3 SMAN 1 Mojosari by using test instrument with subject matter about Introduction (Kennenlernen). From the results of research conducted, found frequent errors include writing point punctuation as in the phrase "Danke, prima und du ?, the error is also done on the comma punctuation as in the phrase" Auf Wiedersehen Kevin "